A COUNTER-RADICALISM MODEL BASED ON THE RESILIENCE OF THE FAMILY OF FORMER TERRORISM CONVICTS: INTEGRATION OF THE LEGAL SYSTEM BY LAWRENCE M. FRIEDMAN AND MAQASHID AL-USRAH JAMALUDDIN ATHIYAH - Umi Sumbulah; Musataklima Musataklima; Zaenul Mahmudi; Khairul Umam; Prayudi Rahmatullah; Handoko Budi Prasetiyo (JURNAL HAKAM, 2026)
Post-deradicalization radicalism remains a serious concern, particularly when former terrorism convicts return to their families and communities. This article analyzes the strengthening of family resilience as a counter-radicalization model for former terrorism convicts in Sampang Regency, Indonesia. This study employed an empirical qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving former terrorism convicts, family members, local government officials, security actors, religious leaders, and socio-religious organizations. The data were analyzed using Lawrence M. Friedman’s legal system theory and Jamaluddin Athiyah’s Maqashid al-Usrah perspective. The findings reveal that family resilience plays a strategic role in preventing the risk of re-radicalization through the strengthening of family communication, economic stability, moderate religious education, psychosocial support, and social acceptance. From Friedman’s perspective, the effectiveness of counter-radicalization depends on the synergy between legal structure, legal substance, and legal culture. Meanwhile, the Maqashid al-Usrah perspective affirms that family strengthening is aligned with the protection of religion, life, intellect, lineage, family institutions, and family economic stability. This article offers a family resilience-based counter-radicalization model that integrates the legal system approach and Maqashid al-Usrah as a conceptual contribution to the prevention of violent extremism in the post-deradicalization phase.